2003
DOI: 10.1081/lpr-120026452
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Peptidoglycans and Adamantyltripeptides into Liposomes: An HPLC Assay for Determination of Encapsulation Efficiency

Abstract: The encapsulation of different immunomodulating peptides, the peptidoglycan monomer, its semisynthetic derivatives (Adamant-1-yl)-acetyl-peptidoglycan monomer and Boc-Tyr-peptidoglycan monomer, respectively, and of two diastereoisomers of adamantyltripeptides into the large negatively charged multilamellar liposomes was investigated. The reproducible quantitative method using HPLC was established for the determination of the entrapped compounds. It was shown that the tested compounds could be efficiently incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…It is non-toxic and non-pyrogenic and thus suitable for potential use with human and veterinary vaccines. In our previous studies adjuvant activity of PGM in different experimental models has been demonstrated (Tomašic et al, 2000;Halassy Špoljar et al, 2002, Halassy et al, 2003Ljevakovic et al, 2003) and its encapsulation into negatively charged, multilamellar liposomes studied (Tomašic et al, 1982;Frkanec, Noething-Laslo et al, 2003;Frkanec, Travaš et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…It is non-toxic and non-pyrogenic and thus suitable for potential use with human and veterinary vaccines. In our previous studies adjuvant activity of PGM in different experimental models has been demonstrated (Tomašic et al, 2000;Halassy Špoljar et al, 2002, Halassy et al, 2003Ljevakovic et al, 2003) and its encapsulation into negatively charged, multilamellar liposomes studied (Tomašic et al, 1982;Frkanec, Noething-Laslo et al, 2003;Frkanec, Travaš et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…The entrapment efficiency of OVA, PGM and Ad2TP2 in mannosylated liposomes was determined in accordance with previously developed methods. [34,36] The results of entrapment efficiency of OVA, PGM and Ad2TP2 into mannosylated liposomes are presented in Table 2.…”
Section: Determination Of the Entrapment Efficiency Of Ova And Immunomentioning
confidence: 99%
“…[31,34] Briefly, eggphosphatidylcholine, cholesterol and mannosyl-lypoconjugates (1, 2 or 3) in a molar ratio of 7 : 5 : 0,5 were dissolved in chloroform : methanol (2 : 1). The chloroform and methanol were evaporated to dryness under vacuum on a rotary evaporator, and then lipid film was hydrated with OVA in saline, concentration 1 mg/mL by gentle hand shaking.…”
Section: Preparation Of Mannosylated Liposomes Formulationsmentioning
confidence: 99%
“…The coupling rate is an important index that reflects the quality of the immunoliposome. It is also influenced by many factors, including the coupling method, antibody type, and liposome quality [13]. The coupling rate of anti-VEGFR to the urea immunoliposome was 36.84%; it is expected that this can be further improved by optimizing the coupling conditions.…”
Section: Discussionmentioning
confidence: 99%